Incidence of Serious Bacterial Infections in Ex-premature Infants with a Postconceptional Age Less Than 48 Weeks Presenting to a Pediatric Emergency Department - Inoue, Nobuaki (Western Journal of Emergency Medicine, 2009)
Objectives: Premature infants are at higher risk of developing serious bacterial infections (SBI). However, the incidence of SBI in ex-premature infants presenting to the emergency department (ED) remains undetermined. The objective of this study is to examine the incidence of SBI in ex-premature infants with a postconceptional age of less than 48 weeks presenting to a pediatric ED.Methods: A retrospective medical record review was conducted on 141 ex-premature infants with a postconceptional age of less than 48 weeks who had a full or partial septic work up completed in a pediatric ED between January 1, 1998 and March 31, 2005.Results: The overall median gestational age at birth was 35 weeks (IQR 33-36 week) and the overall median postconceptional age at ED presentation was 40 weeks (IQR 37-42 weeks). Thirteen (9.2%) infants were found to have a SBI. Five subjects had pneumonia, four with bacteremia, two with pyelonephritis, and two with a concomitant infection of meningitis/pneumonia and bacteremia/pyelonephritis.Conclusion: The results of this study reveal that the incidence of SBI in ex-premature infants with a postconceptional age of less than 48 weeks is similar to in-term infants (9.2%) and is consistent with previously published incidence rates in-term infants (10%).[WestJEM. 2009;10:37-40.]